Risk capability building post Covid-19 through improving competency in risk management - Antonius Alijoyo; Victor Riwu Kaho (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to understand how a pioneer Bus Rapid Transit (BRT) company in Indonesia strengthens its business resilience when facing uncertainty due to the COVID-19 pandemic. A qualitative research approach with the case study method is used where the primary data source is respondents, who are determined based on the purposive sampling method. Data collection and analysis were conducted using triangulation techniques by distributing questionnaires, structured interviews, and focus group discussions, which have helped discover that the pioneer BRT company is not fully prepared for the COVID-19 pandemic. The company then decided to strengthen risk management capabilities by increasing risk management competencies that support decision-making in responding to the impact of the COVID-19 pandemic. Risk leaders believe that strengthening risk capabilities can boost the company's resilience in the face of the COVID-19 pandemic and help it succeed in the new-normal era later. However, it is recommended that companies implement a business continuity management system based on the ISO 22301:2019 Business Continuity Management System (BCMS) standard as a systematic and comprehensive approach. The implication of implementing this standard is strengthening the company's readiness to deal effectively with risks of resilience and business continuity in the future.